Use of Modern Innovative Technologies in Teaching English - Nishonov Ismoiljon Abdumutallibovich (Peerian Journals Publishing, 2022)
This article describes the importance attached to foreign languages in the Republic of Uzbekistan and the innovative technologies needed to study them.
Keywords: Foreign language; game; innovative technology; technological tools